A snowy day in Oakland [videorecording (DVD)] - Bass, Kim; Parker, Nicole Ari; David, Keith; Cole, Deon; Devine, Loretta; Elise, Kimberly, 1971-; Plana, Tony, 1952-; Ross, Evan; Wilson, Reno; White, Michael Jai; Zevallos, Claudia; Gibbs, Marla, 1931- (Strand Releasing Home Entertainment, 2023)
It is centered around Latrice Monroe, a therapist who decides to end a stalled romance with her longtime, high-profile, psychiatrist, boyfriend/business partner. She movies into a predominately African-American and psychologically ignored neighborhood and navigates her practice, he relationships, and her sanity with the town's biggest personalities Davis, Jeanette, and Theona. Her private practice is located in a vacant, street-front office space in the middle of a small, commercial block located across the bay in Oakland turning the neighborhood on its emotional ear.